The Principles of The Kelud Community in Disaster Management - Vitaria Wahyu Astuti; Rimawati Rimawati (Babali Nursing Research, 2021)
Introduction: Natural disasters often occur in Indonesia have prompted the Indonesian government to organize community-based disaster risk reduction which aims to make all Indonesian people resilient in dealing with disasters. The Kelud community is a disaster-resilient community capable of living in peace with disasters and able to immediately rise after experiencing a disaster. The purpose of this study was determined the principles of disaster management in the Kelud community. Methods: This study was a qualitative design with a phenomenological approach. The population in this study were people living close to Mount Kelud, namely Wonorejo Village, Kepung District, and Kebonrejo Village, Puncu District. This study used purposive sampling totaling 15 participants. Data were collected by means of a Focus Group Discussion using an online interview guide, trustworthiness was performed by data triangulation. Results: Data analysis found three themes in the coping principles 1) Fast and precise principles, 2) Priority principles, and 3) Communication and coordination principles. Participants followed the discussion process well, answering questions based on experiences carried out in disaster management. Conclusion: The community is able to implement the principles of disaster management according to the knowledge and skills they have acquired at the training held by the Regional Disaster Management Agency, Jangkar Kelud, and based on the experiences carried out when Mount Kelud erupted.